Free tissue transfer with supermicrosurgical perforator-to-perforator (P-to-P) technique for tissue defect reconstruction around the body: Technical pearls and clinical experience. Issue 8 (August 2021) - Scaglioni, Mario F.; Meroni, Matteo; Fritsche, Elmar
Abstract: Background: Resorting to perforators as recipient vessels is a valid alternative that might offer a series of advantages in many situations. They allow the use of a shorter pedicle, reduce the time of dissection, and are a good solution when deep vessels are difficult to reach. The aim of this study is to investigate the efficacy of P-to-P tissue transfer for reconstructing defects in different areas of the body. Patients and Methods: Between April 2018 and February 2020, 40 patients presenting soft tissue defects were reconstructed by using P-to-P-anastomosed free flap transfer. The cause of the defect was trauma in 16 cases and surgically excised tumor in 24. Five defects were located in the upper extremities, 1 in the neck, 1 in the thorax, and 21 in the lower limb, and 13 cases were breast reconstructions, 2 of which bilateral (43 total flaps). Results: Of all 43 flaps, 22 were abdominal flaps, 17 flaps were harvested from the upper thigh, and 4 were harvested from the lower leg. At the 9 month follow-up, 42 flaps were successfully healed, 36 without complications, 3 after wound dehiscence, and 3 after wound infection, and only 1 flap was lost requiring further surgery. Flap failure rate was 2.3%. Conclusions: Free flaps anastomosed in perforator-to-perforator fashion can be safely used in different settings throughout the body. Even if they are technically more demanding, they may allow a quicker operation time and lower morbidity. With the developments in microsurgical instruments, we believe that this technique may become the gold standard for tissue-defect reconstruction.